2021
DOI: 10.1111/petr.13963
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric discard risk index for predicting pediatric liver allograft discard

Abstract: There is a shortage of pediatric liver allografts available for transplantation, and at the same time, there are over 100 allografts discarded each year. In 2006, the DRI was developed using donor factors and cold ischemia time to predict liver graft failure. 1 However, the DRI has little clinical relevance due to its poor predictive capacity. [2][3][4][5] Because of this poor predictive capacity, marginal allografts are accepted based on the surgeon's subjective assessment of the donor allograft at the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Additionally, a similar analysis exists for pediatric liver transplant 14 . These studies found similar risk factors such as donor age, liver enzymes, LVEF, and donor HBV or HCV antibody status, among other factors 14 . Our analysis showed that high LVEF increases the likelihood of non‐utilization.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Additionally, a similar analysis exists for pediatric liver transplant 14 . These studies found similar risk factors such as donor age, liver enzymes, LVEF, and donor HBV or HCV antibody status, among other factors 14 . Our analysis showed that high LVEF increases the likelihood of non‐utilization.…”
Section: Discussionsupporting
confidence: 74%
“…14 These studies found similar risk factors such as donor age, liver enzymes, LVEF, and donor HBV or HCV antibody status, among other factors. 14 Our analysis showed that high LVEF increases the likelihood of non-utilization. This finding is unique and seemingly paradoxical that cannot easily be explained by current literature or clinical understanding.…”
Section: Pediatric Dsri Predicts Pediatric Heart Allograft Non-utiliz...mentioning
confidence: 68%
See 3 more Smart Citations